Biogas Technology in South Africa, Problems, Challenges and Solutions - Mukumba, Patrick; Makaka, Golden; Mamphweli, Sampson (International Journal of Sustainable Energy and Environmental Research, 2016)
Biogas is a gas that is produced from the biodegradation of organic materials. It consists mainly of methane and carbon dioxide. The biogas from anaerobic digestion can be a solution to South Africa’s energy problems. It can be used for electricity generation, cooking and as transport fuel. There are over 200 biogas digesters scattered across South Africa and the use of biogas is not growing fast in the country irrespective of its benefits in reducing energy related problems such as pollution and energy shortage. This paper reviews biogas technology in South Africa and highlights the problems, challenges and solutions to the expansion of the technology. The research was conducted by surveying biogas digesters installed in the country and measuring the biogas potential from selected digesters. The problems and challenges to biogas technology expansion in the country include; lack of research work on biogas technology, low efficiency of biogas as compared to conventional fuels such as diesel and petrol, cheap electricity cost from coal fired thermal power stations, large amounts of hydrogen sulphides in biogas that can cause corrosion to biogas pipes and internal combustion engines. It was highlighted that biogas digesters to be installed in the country should be sized in accordance with the availability of substrate. In addition, the calorific value of the biogas should be improved so that it can be used to fuel internal combustion engines and generator sets. It was also revealed that community based education on biogas production and its usage need to be initiated so as to reduce biogas digester failures. This would improve biogas technology expansion in the country.